Low genetic variability in Sclerotinia sclerotiorum populations from common bean fields in Minas Gerais State, Brazil, at regional, local and micro‐scales. (8th January 2015) - Lehner, M. S.; Paula Júnior, T. J.; Hora Júnior, B. T.; Teixeira, H.; Vieira, R. F.; Carneiro, J. E. S.; Mizubuti, E. S. G.
<x xml:space="preserve">Abstract</x> Sclerotinia sclerotiorum, causal agent of white mould, is the most destructive and widely distributed soilborne pathogen of common bean during the autumn–winter season in Brazil. Nevertheless, little is known about the genetic structure of the pathogen population. Microsatellite (SSR) markers and mycelial compatibility groups (MCGs) were used to characterize 118 isolates collected from 20 bean fields located in the most important growing regions of Minas Gerais State (MG). Additionally, the genetic variability among 10 isolates obtained from a single sclerotium was investigated in 10 different sclerotia. Seventy SSR haplotypes and 14 MCGs were identified among the 118 isolates. The genetic differences within bean growing areas accounted for most of the genetic variation (72%). Despite the relatively high genotypic diversity, the SSR loci were at linkage disequilibrium. Moreover, 70% of the isolates were assigned to only two MCGs, and haplotypes of a given MCG were closely related. The discriminant analysis of principal components revealed five groups. There was strong genetic differentiation between isolates collected in one municipality in southern MG when compared to other regions. Common bean resistance to white mould should be assessed with representative isolates of the five genetic groups and, if possible, of the different MCGs detected in the present study. One to five haplotypes were detected among the 10 isolates obtained from a single sclerotium. Therefore, in order to ensure genetic identity of an isolate, hyphal tip or monoascosporic isolates should be used.